How Stella got her groove back - McMillan, Terry (New York : Viking, 1996)
A holiday in Jamaica turns into sizzling romance for 42-year-old Stella Payne, a black divorcee and financial security analyst, when she meets Winston Shakespeare, a local assistant cook. Stella invites him to San Francisco to show him off to friends and to her 11-year-old son, and Shakespeare is a hit. Only problem, Shakespeare is 20 years old.
NLJCols20082021
Keywords: African American women -- Fiction; Americans -- Jamaica -- Fiction; Divorced women -- Fiction; Jamaica -- Fiction; Friendship -- Fiction; African American women; Americans; Divorced women; Jamaica; Love stories; African American women -- Fiction; Man-woman relationship -- Fiction; Jamaica -- Fiction; Love stories; Love stories; Love stories; Romance fiction; Fiction; Love stories; Romance fiction; Fiction